Prevalence and Outcomes for Heavily Treatment-Experienced Individuals Living With Human Immunodeficiency Virus in a European Cohort. (1st June 2021) - Pelchen-Matthews, Annegret; Borges, Álvaro H.; Reekie, Joanne; Rasmussen, Line D.; Wiese, Lothar; Weber, Jonathan; Pradier, Christian; Degen, Olaf; Paredes, Roger; Tau, Luba; Flamholc, Leo; Gottfredsson, Magnus; et al.
Abstract : Background: Although antiretroviral treatments have improved survival of persons living with HIV, their long-term use may limit available drug options. We estimated the prevalence of heavily treatment-experienced (HTE) status and the potential clinical consequences of becoming HTE. Setting: EuroSIDA, a European multicenter prospective cohort study. Methods: A composite definition for HTE was developed, based on estimates of antiretroviral resistance and prior exposure to specific antiretroviral regimens. Risks of progressing to clinical outcomes were assessed by Poisson regression, comparing every HTE individual with 3 randomly selected controls who never became HTE. Results: Of 15, 570 individuals under follow-up in 2010–2016, 1617 (10.4%, 95% CI: 9.9% to 10.9%) were classified as HTE. 1093 individuals became HTE during prospective follow-up (HTE incidence rate 1.76, CI: 1.66 to 1.87 per 100 person-years of follow-up). The number of HTE individuals was highest in West/Central Europe (636/4019 persons, 15.7%) and lowest in East Europe (26/2279 persons, 1.1%). Although most HTE individuals maintained controlled viral loads (<400 copies/mL), many had low CD4 counts (⩽350 cells/µL). After controlling for age, immunological parameters and pre-existing comorbidities, HTE status was not associated with the risk of new AIDS (adjusted incidence rate ratio, aIRR 1.44, CI: 0.86 to 2.40, P = 0.16) or non-AIDS clinical events (aIRR 0.96, CI: 0.74 to 1.25, P = 0.77). Conclusions: HTE prevalence increased with time. After adjusting for key confounding factors, there was no evidence for an increased risk of new AIDS or non-AIDS clinical events in HTE. Additional therapeutic options and effective management of comorbidities remain important to reduce clinical complications in HTE individuals. Abstract : Supplemental Digital Content is Available in the Text.